Virtual Postgraduate Open Week (VOW) - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2021)
The 1st series of VOW for the year 2021 has been conducted from 25th - 29th January 2021 from 10.00 am until 6.00 pm. A total of 20 live webinar series have been conducted successfully during the VOW. This manages to attract a total of 432 potential candidates who participated using various online base platforms (Google meet, Webex meet, Facebook, and Microsoft Team) prepared by IPSis and faculty representative. Mainly, it is also noted the participant that participated during the VOW is from the various background which is a mixture of national and international candidates. Active interaction between the faculty representative and candidates has been carryout during the VOW. Generally, an energetic live discussion introduced a new Master's and Ph.D. program from diverse faculty in UiTM. This discussion has attracted huge attention particularly the candidate notices the career opportunities as soon as completing the Master or Ph.D. program offered by UiTM. Besides, the faculty representative also takes a good prospect to introduce Master and Ph.D. programs from each faculty that always get the highest demand amount the employee in the national and international market.